Isolation and Characterization of Cellulose from Biomass: A Methodological Review - Aisyah Hanifah; Riska Sumirat; Sarah Fitri Soerya; Manggar Arum Aristri (Agroindustrial Technology Journal, 2025)
The isolation and characterization of cellulose from biomass have garnered increasing research interest due to cellulose’s pivotal role in supporting sustainable material innovations across various industries. This study presents a comprehensive review of recent advancements in cellulose isolation methods, including chemical, mechanical, and enzymatic techniques, emphasizing their efficiencies in yield and purity. A bibliometric analysis using VOSviewer was also conducted to map research trends, identify leading authors and institutions, and visualize keyword co-occurrence networks from publications between 2015 and early 2025. The bibliometric results revealed three major thematic clusters in cellulose research: extraction and pretreatment technologies, material characterization techniques, and structural property analysis. Publication trends indicated dynamic research developments, particularly a surge in interest following advances in green extraction technologies. Overall, this review highlights the shift towards sustainable cellulose isolation strategies, evaluating the advantages and disadvantages of various methodologies. It provides insights into the strengths and limitations of current techniques, while also outlining potential future directions for research and industrial applications.